Adolescence and love relationships: a study of Rio de Janeiro’s lower class teenagers - Terezinha Féres-Carneiro; Bernardo Jablonski (Interação em Psicologia, 2005)
On the present study the conceptions and experiences of love relationships, among lower class teenagers from Rio de Janeiro, were investigated. A semi-structured interview was used, including themes such as dating, flirting, and perspectives on future marriage and family formation. First, a review of adolescence as a theoretical construct was realized in the psychoanalytical literature, including its developmental characteristics, and then, love relations were reviewed following its transformation throughout history. The major research findings were and compared to contemporary forms of romantic relationships. Finally, the results of the present study were presented and discussed. Results stressed teenagers desire for long-term relationships, based on mutual affect, specially made possible through the “ficar” relationship, that means flirting, in which partners could increase their mutual knowledge. Keywords: adolescence; lower-class teenagers; love relationships; dating.